Acidification of phosphate buffered saline - Veselý, Lukáš; Susrisweta, Behera; Štůsek, Radim; Mužík, David; Heger, Dominik (International journal of pharmaceutics, 2025)
It has been demonstrated that freezing-induced acidity changes have an impact on the structural integrity, degree of aggregation, and chemical stability of frozen food and pharmaceutical products. The stability of the compounds in solutions is maintained by the presence of buffers. However, many buffers are unsuitable for applications involving freezing as this process substantially alters the acidity. In this study, we determine the effect of initial pH, concentration, and cooling rate on the freezing-induced change in acidity of phosphate buffered saline (PBS) in the frozen state via UV-VIS spectroscopy. Furthermore, we examine the impact of individual salts present in PBS and discuss the mechanisms affecting the resulting acidity that we approximate via Hammett acidity function (H2-).
Keywords: Preferential precipitation; Acidification; zmrazování; Buffers; Phosphates; PBS; Hydrogen-Ion Concentration; Saline Solution; koncentrace vodíkových iontů; pufry; Freezing; solný roztok; Buffering capacity; fosfáty